Prevalence and associated factors of depression and anxiety among patients with melasma: a cross-sectional study in China - Chen, Wenjing; Fang, Runan; Zhang, Kaihui; Shen, Yang; Sun, Yuan; Gao, Jiacheng; Zhai, Ye; Sun, Liuhong; Li, Jianhong (Frontiers in Psychiatry, 2025)
BackgroundMelasma is a common acquired skin hyperpigmentation disorder characterized by light to dark brown macules and patches, predominantly on the face. Due to its visible nature, the condition often imposes substantial psychological and emotional burdens on affected individuals. Depression and anxiety are common conditions that occur in patients suffering from melasma; however, comprehensive data regarding their prevalence and associated factors remain scarce. This cross-sectional observational study aimed to assess the prevalence of depression and anxiety in patients with melasma and identify potential associated factors.MethodsA total of 264 melasma patients were recruited for the study between July 2023 and May 2024. Depression and anxiety were assessed using the Self-rating Depression Scale (SDS) and the Self-rating Anxiety Scale (SAS), respectively. Univariate and multivariate logistic regression analyses were conducted to determine variables associated with depression and anxiety among patients with melasma.ResultsThe study revealed a prevalence of 33.3% (95% CI: 27.610-39.057) for depression and 21.6% (95% CI: 16.595-26.587) for anxiety among melasma patients. Age ≥ 45 years, high BMI and poor quality of life were identified as factors independently associated with depression in patients with melasma. Poor sleep quality was found to be an independently relative factor for anxiety among patients with melasma.ConclusionsThe prevalence of depression and anxiety was higher among patients with melasma. Depression was negatively correlated with the older but positively correlated with high BMI and poor quality of life. Anxiety was positively associated with poor sleep quality. On the basis of these findings, the present study suggests that routine screening for depression and anxiety should be conducted in patients with melasma to facilitate early intervention strategies. Such targeted approaches may not only enhance treatment outcomes but also significantly improve patients’ overall quality of life.